Relationship of sanitation, water boiling, and mosquito nets to health biomarkers in a rural subsistence population. Issue 1 (10th December 2019) - Dinkel, Katelyn A.; Costa, Megan E.; Kraft, Thomas S.; Stieglitz, Jonathan; Cummings, Daniel K.; Gurven, Michael; Kaplan, Hillard; Trumble, Benjamin C.
Abstract: Objectives: Throughout human evolutionary history, parasites and pathogens were a major cause of mortality‐modern urban life with public health infrastructure has changed disease exposure. We examine associations between boiling water, using latrines, mosquito net usage, and biomarkers among the Tsimane, a nonindustrial subsistence population with little public health infrastructure. Methods: We conducted cross sectional surveys on water, latrines, and bed nets among 507 heads of households (aged 18‐92 years, median age 41 years). Regression models estimated associations between behaviors and health biomarkers (ie, white blood cell count [WBC], hemoglobin, eosinophil count, and erythrocyte sedimentation rate) adjusting for age, sex, body mass index, wealth, schooling, and distance to the nearby market town. Results: Latrine use is associated with 6.5% lower WBC count (β = −679.6, P = .031, SE = 314.1), 17.4% lower eosinophil counts (β = −244.7, P = .023, SE = 107.2), and reduced odds of eosinophilia (adjusted OR = 0.40, P < .019, 95% CI = 0.18‐0.86). Boiling water and mosquito net use are not significantly associated with any biomarkers measured. Conclusions: In a subsistence population currently undergoing epidemiological transition, we find that latrine use was associated with several objective measures of health. This suggests that relatively low cost and low maintenance public health interventions may wish to focus on latrine use, as there is unmet need and potential health benefits for those who use latrines. Additionally, while the cost is higher, public health organizations aimed at improving sanitation may be able to use minimally invasive field‐collected biomarkers as a diagnostic to objectively test the efficacy of interventions with greater specificity than anthropometric measurements.